Inovasi Produk dan Pendampingan Ijin Produk pada Kelompok Masyarakat Guna Meningkatkan Perekonomian - Kunti Nastiti; Setia Budi; Melviani Melviani; Samsul Hadi (Indonesia Berdaya, 2023)
The Covid-19 pandemic has caused small businesses throughout Indonesia to experience an economic decline. People are psychologically afraid of contracting the virus, so they limit going out of the house. Indirectly causing a decrease in income because people limit spending and consumption patterns. This community service aims to help community small businesses located in Banjarbaru, South Kalimantan in managing their business. The survey results stated that there was a decline in sales, especially in the food, salon, cosmetic product, stalls and other clothing sales. The obstacle faced by this business unit is the absence of product innovation that adapts to pandemic conditions. Another thing in marketing products is that many people do not know about strategies regarding promotion, branding, product advertising, product legalization and other strategies. The forms and methods that are the solution to this activity are product innovation related to herbal products and providing knowledge about the legality of products, both herbal products and food products that have been produced so that they are expected to be widely marketed. Apart from that, providing knowledge about product marketing strategies through online promotion and branding as well as providing knowledge on how to have a good managerial system. Herbal product innovation has increased during the Covid-19 pandemic because several herbs are believed to help the body's resistance to disease.